Pemphigus Vulgaris: Short Time to Relapse in Patients Treated in a Danish Tertiary Referral Center - Mohamad, Aheen Faisal; Iversen, Lars; Bech, Rikke (Frontiers in Medicine, 2019)
Pemphigus vulgaris is an autoimmune skin disorder with development of blisters in the skin and mucosa, and it can be a life-threatening disease if not treated. Corticosteroids have been a cornerstone for treating PV, but because of side effects the treatment is combined with other conventional immune modulating drugs and rituximab. The Danish treatment protocol for pemphigus vulgaris is similar to the other Scandinavian countries, and therefore this study is of importance for clinicians in the Scandinavian countries as well as other European contries. We retrospectively identified all patients with Pemphigus vulgaris in our tertiary centre over a 7-year period in order to register patient characteristics, treatment, adverse events, comorbidities and the effect of prednisolone dose on remission. In this study 19 patients met the inclusion criteria and remission was seen after a mean of 19,9 weeks, and relapse was seen in 50 % after the mean time of 15 weeks. Time to relapse in our study is relatively short compared to studies in which rituximab is used as a first-line drug in treating pemphigus vulgaris.